Iluminasi dalam Naskah Cirebon - Achmad Opan Safari (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Illumination of the manuscript is an integral part of the manuscritpt itself. Illumination of the manuscript can help readers understand the origin of the manuscripts as the characteristic and pattern of the motive of the manuscripts of each region is different from one to another, besides indeed the style and the subjectivity of the writer. One of the regions which has the manuscripts with various illumination is Cirebon, a border area between two poles of the two big cultures: Java and Sunda. The tradition of making manuscript illumination is developed in line with the tradition of the writing and rewriting the manuscripts. The illumination is made based on the contain of the text or the adjustment of the genre of the manuscript. This writing is discussing various types of the illumination and their functions in the manuscript and social-economic of Cirebon community.